Fibroblast Growth Factor 2 Protein Stability Provides Decreased Dependence on Heparin for Induction of FGFR Signaling and Alters ERK Signaling Dynamics - Koledova, Zuzana; Sumbal, Jakub; Rabata, Anas; de La Bourdonnaye, Gabin; Chaloupkova, Radka; Hrdlickova, Barbara; Damborsky, Jiri; Stepankova, Veronika (Frontiers in Cell and Developmental Biology, 2019)
Fibroblast growth factor 2 (FGF2) plays important roles in tissue development and repair. Using heparan sulfates (HS)/heparin as a cofactor, FGF2 binds to FGF receptor (FGFR) and induces downstream signaling pathways, such as ERK pathway, that regulate cellular behavior. In most cell lines, FGF2 signaling displays biphasic dose-response profile, reaching maximal response to intermediate concentrations, but weak response to high levels of FGF2. Recent reports demonstrated that the biphasic cellular response results from competition between binding of FGF2 to HS and FGFR that impinge upon ERK signaling dynamics. However, the role of HS/heparin in FGF signaling has been controversial. Several studies suggested that heparin is not required for FGF-FGFR complex formation and that the main role of heparin is to protect FGF from degradation. In this study, we investigated the relationship between FGF2 stability, heparin dependence and ERK signaling dynamics using FGF2 variants with increased thermal stability (FGF2-STABs). FGF2-STABs showed higher efficiency in induction of FGFR-mediated proliferation, lower affinity to heparin and were less dependent on heparin than wild-type FGF2 (FGF2-wt) for induction of FGFR-mediated mitogenic response. Interestingly, in primary mammary fibroblasts, FGF2-wt displayed a sigmoidal dose-response profile, while FGF2-STABs showed biphasic response. Moreover, at low concentrations, FGF2-STABs induced ERK signaling more potently and displayed faster dynamics of full ERK activation and higher amplitudes of ERK signaling than FGF2-wt. Our results suggest that FGF2 stability and heparin dependence are important factors in FGF-FGFR signaling complex assembly and ERK signaling dynamics.